A Comprehensive Review on the Recent Advances in the Valorization of Jackfruit Waste for the Development of Value-Added Products - Brahma, Rangina; Ray, Subhajit (Journal of Food Technology Research, 2022)
The jackfruit (Artocarpus heterophyllus), a particular member of the Moraceae family, is abundantly found in Asia’s tropical and subtropical regions, and it has been reported to have a range of useful properties that treat ailments. Jackfruit contains both edible fractions e.g. seed and inedible fractions e.g. peel, rags, latex, perianth, core which are generally disposed of into the environment directly as waste and thereby causing an environmental concern as it leads to bio-waste accumulation. The existence of multiple beneficial compounds in the discarded parts of fruit contributes to its usage as a raw material in various food products such as bread, cake, cookies, extruded products, etc and also in various other sectors such as the fuel, cosmetics, pharmaceutical industries etc. This literature analysis was conducted to gain a good comprehension of changing trends in the Jackfruit waste utilization scenario, shaping up into the formation of value added food products. This review paper is designed by considering some latest findings of several researchers in this area.